2008
DOI: 10.1128/iai.01143-07
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Immune Polarization Patterns Is Linked to Resistance versus Susceptibility toCryptococcus neoformansin a Mouse Model

Abstract: Genetic background variation between inbred strains accounts for different levels of susceptibility to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
113
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(133 citation statements)
references
References 40 publications
10
113
0
Order By: Relevance
“…The early changes in cytokine expression direct subsequent immune polarization in C. neoformans-infected mice. 7,11,21,26 We found that mRNA induction levels for pro-Th1 IL-12p35 and pro-Th17 IL-23p19 were significantly higher in IL-4/ 13 Ϫ/Ϫ compared with wild-type mice at week 1 (1.64 Ϯ 0.53 versus 0.37 Ϯ 0.04 and 1.36 Ϯ 0.22 versus 0.46 Ϯ 0.01, respectively). In contrast, p40 shared by IL-12 and IL-23, but also forming inhibitory p40(2) homodimer, was Ϫ/Ϫ and wild-type) were infected with 10 4 CFU via the intratracheal route with C. neoformans H99 and analyzed at weeks 2 and 3 postinfection.…”
Section: Combined Deletion Of Il-4 and Il-13 Prevented Th2 And Promotmentioning
confidence: 83%
See 3 more Smart Citations
“…The early changes in cytokine expression direct subsequent immune polarization in C. neoformans-infected mice. 7,11,21,26 We found that mRNA induction levels for pro-Th1 IL-12p35 and pro-Th17 IL-23p19 were significantly higher in IL-4/ 13 Ϫ/Ϫ compared with wild-type mice at week 1 (1.64 Ϯ 0.53 versus 0.37 Ϯ 0.04 and 1.36 Ϯ 0.22 versus 0.46 Ϯ 0.01, respectively). In contrast, p40 shared by IL-12 and IL-23, but also forming inhibitory p40(2) homodimer, was Ϫ/Ϫ and wild-type) were infected with 10 4 CFU via the intratracheal route with C. neoformans H99 and analyzed at weeks 2 and 3 postinfection.…”
Section: Combined Deletion Of Il-4 and Il-13 Prevented Th2 And Promotmentioning
confidence: 83%
“…After inoculation, the skin was closed with cyanoacrylate adhesive. 8,26 Organ CFU assay For determination of microbial burden in the lungs, small aliquots of dispersed lungs were collected following the digest procedure. For determination of brain and spleen CFU, the brains and spleens were dissected using sterile instruments, placed in 2 ml of sterile water, and homogenized.…”
Section: Il-4/13mentioning
confidence: 99%
See 2 more Smart Citations
“…31,32,37 We used six-to eight-parameter flow cytometric analysis to assess the relative prevalence and phenotype of AMs and ExMs during the pre-effector and effector phases of the host response to infection and determined whether AMs or ExMs proliferate in the lungs of infected mice. We then performed a comparative analysis using gene-targeted mice deficient in CCR2 (CCR2 Ϫ/Ϫ mice; BALB/c genetic background) to determine whether accumulation of ExMs requires the recruitment and differentiation of blood monocytes.…”
mentioning
confidence: 99%